2013
DOI: 10.1115/1.4023562
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Jet-to-Plate Spacing of Inline Impingement Heat Transfer for Different Crossflow Schemes

Abstract: A nine-by-nine jet array impinging on a flat plate at Reynolds numbers from 15,000 to 35,000 has been studied by the transient liquid crystal method. The spacing between the impingement plate and target plate is adjusted to be 1, 2, 3, 4, and 5 jet diameters. The effect of jet-to-plate spacing has been investigated for three jet-induced crossflow schemes, referred as minimum, medium, and maximum crossflow, correspondingly. The local air jet temperature is measured at several positions on the impingement plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…Generally, the best designs are in the range of H/d= 2-5, S/d= 6.5-10, θ = 60-90°, Vj = 44-50 m/s and Vw = 0.17-7 m/s. These results also have a correlation with literature for optimum value of design parameters for maximum area-averaged Nu number [3,7,11,13,14,17].…”
Section: Relative Surface Velocitysupporting
confidence: 82%
See 1 more Smart Citation
“…Generally, the best designs are in the range of H/d= 2-5, S/d= 6.5-10, θ = 60-90°, Vj = 44-50 m/s and Vw = 0.17-7 m/s. These results also have a correlation with literature for optimum value of design parameters for maximum area-averaged Nu number [3,7,11,13,14,17].…”
Section: Relative Surface Velocitysupporting
confidence: 82%
“…Badra et al [12] found that the optimal value of H/d=6-7 for the maximum stagnation Nu number from the single impinging jet. Xing and Weigand [13] found that H/d=3 could improve the heat transfer performance for a variety of crossflow configurations. Specht [14] found that for single nozzle arrays and hole channels the maximum heat transfer is at optimum S/d=6.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in some papers (San and Chen, 2014;Yamane, et al, 2012;Mehryara andGiovanninib, 2014, Xing andWeigand, 2013), Nusselt number distribution on impinging wall of MIJ is reported,this distribution is of particular interest to researches. Thus we demonstrate the local heat flux on the impinging wall as the heat transfer performance of the MIJ.…”
Section: Fig 8 Contour Of Instantaneous Velocity Magnitudementioning
confidence: 99%
“…), [6,7] and parameters (shape, number, etc.) [8,9] of the thin plates used. An ultrathick plate has a large thickness, high heat capacity, and long quenching time.…”
Section: Introductionmentioning
confidence: 99%